(untitled) (Malay Studies: History, Culture and Civilization, 2025)
Modern society views ancestral traditions as outdated and prefers western culture which is considered more advanced. The influence of change can be seen from people’s lifestyles and mindsets which have become materialistic. The impact of globalization is such as a moral and ethical crisis. This research uses qualitative methods with research techniques that are library research, namely a research technique whose data sources come from books, notes, reports and so on related to research. The results of this research are expected to open our horizons regarding local traditions in the world of academia or to the general public. The Sebaran Apem tradition contains meaning that can be developed as a moral concept. Among these values "‹"‹are always remembering that as a creature, always asking for forgiveness from Allah and also always having an open-hearted nature. Then the goal of life in this world will ultimately lead to Allah. tolerance and respect for fellow human beings. Mutual help and feelings of brotherhood. tolerant, moderate, mutually helpful.